Construction and Validation of Alternative Usability Scale - Adhikari, Pralhad (Tribhuvan University Journal, 2023)
Usability is the extent of a system being user-friendly. The aim of this research was to make a test to measure usability based on five-factor model of usability by Nielsen (1993). Total of 755 participants (Mage=26.1, SD=5.86) representing the users of 21 types of products or services gave responses. Psychometric analyses were done. The test with fifteen items did not fit the model of its parent theory as revealed by confirmatory factor analysis. Principal component analysis was conducted and some items were deleted. Finally, a test of 12 items with two subscales was made. The participants were given a survey in English but they were not its native speakers. The future research can take native speakers and more diverse products’ or services’ users for psychometric analyses of the 15-item version.